Molecular basis of natural variation and environmental control of trichome patterning - Hauser, Marie-Theres (Frontiers in Plant Science, 2014)
Trichomes are differentiated epidermal cells on above ground organs of nearly all land plants. They play important protective roles as structural defences upon biotic attacks such as herbivory, oviposition and fungal infections and against abiotic stressors such as drought, heat, freezing, excess of light and UV radiation. The pattern and density of trichomes is highly variable within natural population suggesting tradeoffs between traits positively affecting fitness such as resistance and the costs of trichome production. The spatial distribution of trichomes is regulated through a combination of endogenous developmental programs and external signals. This review summarizes the current understanding on the molecular basis of the natural variation and the role of phytohormones and environmental stimuli on trichome patterning.